2013
DOI: 10.3390/s130809896
|View full text |Cite
|
Sign up to set email alerts
|

A Wireless Passive Pressure Microsensor Fabricated in HTCC MEMS Technology for Harsh Environments

Abstract: A wireless passive high-temperature pressure sensor without evacuation channel fabricated in high-temperature co-fired ceramics (HTCC) technology is proposed. The properties of the HTCC material ensure the sensor can be applied in harsh environments. The sensor without evacuation channel can be completely gastight. The wireless data is obtained with a reader antenna by mutual inductance coupling. Experimental systems are designed to obtain the frequency-pressure characteristic, frequency-temperature characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…However, they have been only demonstrated in very low temperatures. More recently, LC resonator, and inductive based coupling have been reported for high temperature applications . Nonetheless, these inductive coupling sensors are restricted in terms of coil orientation, size, and distance to metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have been only demonstrated in very low temperatures. More recently, LC resonator, and inductive based coupling have been reported for high temperature applications . Nonetheless, these inductive coupling sensors are restricted in terms of coil orientation, size, and distance to metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al and Tan et al have demonstrated improvements of the work reported in [22], both in LTCC and HTCC [24,25]. By applying a fugitive paste for support of the diaphragm during the fabrication, the yield was improved, and the resulting sensitivity of the LTCC sensor was 18163 ppm/bar at room temperature for pressures up to 3.6 bars.…”
Section: Introductionmentioning
confidence: 99%
“…Passive pressure sensors based on resistive [4,5] or capacitive [6,7] sensing mechanisms were proposed to survive high temperatures above 400 o C. However, wire interconnection is required to interrogate these sensors, which is main failure mechanism for gas turbine applications [8]. By using capacitive sensing mechanism and inductive coupling, pressure sensors were demonstrated wirelessly for high-temperature applications [9][10][11]. However, quality (Q) factors of LC resonators are usually very limited, especially at high temperatures.…”
Section: Introductionmentioning
confidence: 99%